2017
DOI: 10.1016/j.ejca.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Adding abiraterone to androgen deprivation therapy in men with metastatic hormone-sensitive prostate cancer: A systematic review and meta-analysis

Abstract: BackgroundThere is a need to synthesise the results of numerous randomised controlled trials evaluating the addition of therapies to androgen deprivation therapy (ADT) for men with metastatic hormone-sensitive prostate cancer (mHSPC). This systematic review aims to assess the effects of adding abiraterone acetate plus prednisone/prednisolone (AAP) to ADT.MethodsUsing our framework for adaptive meta-analysis (FAME), we started the review process before trials had been reported and worked collaboratively with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
84
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 19 publications
1
84
1
7
Order By: Relevance
“…Although our results do not provide a definitive assessment, they strongly support these two factors—the number of bone metastases and biopsy Gleason score—as being risk factors for CSS and OS in patients with newly diagnosed mHNPC. However, the present study did not reveal any impact of visceral metastasis on CSS and OS, perhaps because of the small number of patients compared with the numbers included in the previous trials (14.0%‐18%) …”
Section: Discussioncontrasting
confidence: 80%
“…Although our results do not provide a definitive assessment, they strongly support these two factors—the number of bone metastases and biopsy Gleason score—as being risk factors for CSS and OS in patients with newly diagnosed mHNPC. However, the present study did not reveal any impact of visceral metastasis on CSS and OS, perhaps because of the small number of patients compared with the numbers included in the previous trials (14.0%‐18%) …”
Section: Discussioncontrasting
confidence: 80%
“…ADT impacted combined CVD morbidity and the risk of specific CV diseases such as myocardial infarction and ischaemic heart disease. Risk was associated with type(7, 28), adverse event grade (22,23,29) and duration of ADT (71). Cardiac mortality was less common but increased risk was identified for all ADT, ADT monotherapy and GnRH agonists (28).…”
Section: Discussionmentioning
confidence: 99%
“…In other reviews, degarelix reduced the risk of CV events compared to GnRHa, as did IADT (12,15,25). There was a strong association between grade 3 cardiac adverse events and grade 3/4 vascular events and arbiraterone acetate + prednisone compared to placebo (23). This impact was lower for all grade events.…”
Section: Cardiac Disorders: Cardiovascular (Cv) Complications and Mormentioning
confidence: 90%
See 1 more Smart Citation
“…Meta‐analysis of the STAMPEDE and LATITUDE (A study of abiraterone acetate plus low‐dose prednisone plus ADT vs ADT alone in newly diagnosed participants with high‐risk mHNPC) trials studying abiraterone, showed that abiraterone combined with prednisone and ADT resulted in a 38% reduction in risk of death (hazard ratio [HR] 0.62, 95% CI 0.53–0.71) and a 14% increase in overall survival (OS) at 3 years compared with ADT alone . Abiraterone is associated with a two‐fold increase in hypertension and a three‐fold increase in cardiac and hepatic toxicity compared with ADT monotherapy . Hence, it should be avoided in men with uncontrolled hypertension, cardiac failure, pre‐existing liver disease, and poorly controlled diabetes due to use of concomitant prednisone.…”
Section: Dosage Adverse Events and Key Practice Points Associated Wimentioning
confidence: 99%